(untitled) (Bangladesh Journal of Microbiology, 2024)
Aerobic methanotrophic bacteria maintain an unrivalled capability of utilizing methane as their sole carbon and energy source and have been retrieved from various environments. Phylogenetically, true aerobic thermoacidophilic methane oxidizers capable of growing below pH 3 have hitherto been associated only with the phylum Verrucomicrobia. In this report, the initial detection of a moderately thermoacidophilic Methylococcus-like Type Ib methanotroph of the class Gammaproteobacteria from an acidic thermal spring (50oC and pH 2.8) in the Yellowstone National Park, USA is presented. The isolate, termed YT-MC, was identified in a methane enrichment (55°C), which may represent a novel strain in the family Methylococcaceae Type Ib. The existence of this bacterium in the enrichments was demonstrated by the detection of pmoA gene, Southern blotting technique, phase-contrast, and electron microscopy. The coccus-typed cells showed tubular membranes instead of intracytoplasmic membrane systems (ICM). The soluble methane monooxygenase (sMMO) was not detected by PCR, indicating that the biotransformation of methane to methanol is oxidized by the particulate methane monooxygenase (pMMO). Moreover, YT-MC performs in a formerly undiscovered active biological methane sink in geothermal acidic environments, magnifying our knowledge of its ecological role in methane cycling, diversity, and coexistence of aerobic methanotrophy. Furthermore, the present study also reports the isolation and identification of an alphaproteobacterial heterotroph (strain YT-AC) and a verrucomicrobial methanotroph (strain YT-VM) from the same environment. Bangladesh J Microbiol, Volume 40, Number 2, December 2023, pp 86-94